Effect of sildenafil citrate treatment in the eNOS knockout mouse model of fetal growth restriction on long-term cardiometabolic outcomes in male offspring. (November 2018) - Mills, Valerie; Plows, Jasmine F.; Zhao, Huan; Oyston, Charlotte; Vickers, Mark H.; Baker, Philip N.; Stanley, Joanna L.
Graphical abstract: Abstract: Fetal growth restriction (FGR) is associated with an increased risk of hypertension, insulin resistance, obesity and cardiovascular disease in adulthood. Currently there are no effective treatments to reverse the course of FGR. This study used the eNOS knockout mouse (eNOS −/− ), a model of FGR, to determine the ability of sildenafil, a potential new treatment for FGR, to improve cardiovascular and metabolic outcomes in adult offspring following a complicated pregnancy. Pregnant eNOS −/− and C57BL/6J control dams were randomised to sildenafil treatment (0.2 mg/ml in drinking water) or placebo at day 12.5 of gestation until birth. After weaning, male offspring were randomised to either a high fat (HFD; 45% kcal from fat) or normal chow diet (ND), and raised to either postnatal day 90 or 150. Growth and body composition, glucose tolerance, insulin resistance, systolic blood pressure and vascular function were analysed at both time-points. eNOS −/− offspring were significantly smaller than their C57BL/6J controls at weaning and P90 (p < 0.01); at P150 they were a similar weight. Total adipose tissue deposition at P90 was significantly increased only in eNOS −/− mice fed a HFD (p < 0.001). At P150 both C57BL/6J and eNOS -/- offspring fed a HFD demonstrated significant adipose tissue deposition (p < 0.01), regardless of maternal treatment. Both diet and maternal sildenafil treatment had a significant effect on glucose tolerance. Glucose tolerance was significantly impaired in eNOS −/− mice fed a HFD (p < 0.01); this was significant in offspring from both sildenafil and vehicle treated mothers at P90 and P150. Glucose tolerance was also impaired in C57BL/6J mice fed a HFD at both P90 and P150 (p < 0.01), but only in those also exposed to sildenafil. In these C57BL/6J mice, sildenafil was associated with impaired insulin sensitivity at P90 (p = 0.020) but increased insulin resistance at P150 (p = 0.019). Exposure to sildenafil was associated with a significant increase in systolic blood pressure in eNOS −/− mice compared with their C57BL/6J diet controls at P150 (p < 0.05). Exposure to sildenafil had differing effects on vascular function in mesenteric arteries; it increased vasodilation in response to ACh in C57BL/6J mice, but was associated with a more constrictive phenotype in eNOS −/− mice. eNOS −/− mice demonstrate a number of impaired outcomes consistent with programmed cardiometabolic disease, particularly when faced with the 'second hit' of a HFD. Exposure to sildenafil treatment during pregnancy did not increase fetal growth or significantly improve adult metabolic or cardiac outcomes. Maternal sildenafil treatment was, however, associated with small impairments in glucose handling and an increase in blood pressure. This study highlights the importance of understanding the long-term effects of treatment during pregnancy in offspring from both complicated and healthy control pregnancies.